‘ARABNESS’ AS SOCIAL CAPITAL IN MADURA - Mirjam Lucking (UIN Sunan Gunung Djati Bandung, 2014)
The construction of “Self” and “Other” is a crucial element in the conception ofidentity. The practice of ‘othering’ goes along with an orientation towards ‘other’places and is related to the broader perceptions of the world. The ideas of otherplaces become increasingly diverse going beyond binary oppositions of ‘Orient’ and‘Occident’ and “contemporary world-historical processes are disrupting received geographies of core and periphery”. Previous research, done by my colleagues in the research project “Beyond Occidentalism”, in the Freiburg Southeast Asian Studies interdisciplinary research group, has shown that in Indonesia it is no longer the ‘West’ that is the ultimate reference point but a variety of new imagined centres. Among others the ‘Arab World’ appears to be a relevant imagined centre and ‘Arabic style’ is a trend in some contexts, as for instance in Madura. My research project concerns images of the ‘Arab World’ in Indonesia, questioning how people in Indonesia position themselves towards the ‘Arab World’. Initially I started the research in Central Java. During my investigations I was often told that Madurese people are particularly attracted by the ‘Arab World’ and I thus decided to include Madura as a comparative research site in my research.